An Ex-Vivo Study of Photobiomodulation Effects on Hematological and Inflammatory Markers in Breast Cancer Patients - Hussein, Bushra Radhi; AL Timimi, Zahra (Asian Pacific Journal of Cancer Care, 2026)
Introduction: Photobiomodulation with low-level laser therapy has been demonstrated immunomodulatory and anti-inflammatory effects in various clinical settings. However, its systemic effects on hematological parameters in breast carcinoma patients remain underexplored. Objective: To evaluate the impact of LLLT on immune and inflammatory blood markers in breast carcinoma patients, with a focus on fluence-dependent responses based on varying exposure durations. Materials and Methods: One hundred samples of venous blood from breast carcinoma patients were randomly assigned to either a non-irradiated control group or one of the experimental groups that were treated with a laser. Experimental group samples were subjected ex vivo to an 810 nm, 500 mW near-infrared laser for 1, 1.5, 2, and 2.5 minutes, corresponding to energy densities of 30, 45, 60, and 75 J/cm². We compared important hematological measurements total white blood cell (WBC), lymphocyte (LYM), granulocyte percentage (GRA %), hemoglobin content (HGB), and platelet (PLT) and assessed means between groups by one-way ANOVA and suitable post hoc tests. Results: LLLT resulted in a significant decrease in WBC, LYM, HGB, and PLT values across all irradiated samples compared to controls. In contrast, GRA% showed a consistent and significant increase in all laser-treated groups. No dose-response trend was observed among the laser durations, suggesting a threshold biological effect. Conclusion: Ex vivo LLLT alters key hematological indices in blood from breast carcinoma patients, marked by immune cell redistribution and mild erythrocyte suppression. These outcomes support the potential of LLLT to moderate inflammatory in addition to immune responses, warranting further investigation in in vivo and clinical settings.